α-Synuclein in the Synaptic Vesicle Liquid Phase: Active Player or Passive Bystander? - Brodin, Lennart; Milovanovic, Dragomir; Rizzoli, Silvio O.; Shupliakov, Oleg (Frontiers in Molecular Biosciences, 2022)
The protein α-synuclein, which is well-known for its links to Parkinson’s Disease, is associated with synaptic vesicles (SVs) in nerve terminals. Despite intensive studies, its precise physiological function remains elusive. Accumulating evidence indicates that liquid-liquid phase separation takes part in the assembly and/or maintenance of different synaptic compartments. The current review discusses recent data suggesting α-synuclein as a component of the SV liquid phase. We also consider the possible implications of these data for disease.